The Pricing System of Red Onion and Red Chili Commodities - Heny Kuswanti Suwarsinah; Naafi Fatimah Harwanti; Hastuti Hastuti; Muhammad Firdaus (Jurnal Manajemen & Agribisnis, 2018)
The prices of red chili and red onion commodities tend to fluctuate and have high margin rates, causing inefficiency of prices. On the other hand, the demand for red chili and red onion will increase as the number of population increases. This study aimed to analyze the factors and behaviors that can affect the pricing system on red onion and red chili in East Jakarta by using the Vector Error Correction Model and Game Theory. The results showed that the producer and wholesale prices of red onion and red chili commodities contribute to the price discovery at the consumer level. Maximum profit is achieved by retail merchants when they adopt prices in collusion as a dominant strategy.Keywords: red onion, red chili, game theory, price, VECM